Analisis Gerak Partikel dalam Ruang Waktu Lengkung dengan Fungsi Green - Yamin Ismail; Abas Kaluku (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
Motion of particle in curved spacetime as generalization of flat space-time with metric gµʋ the motion in this article is scalar charge q, electric charge e,and particle mass m will produce field that can have the behavior as a radiation zone of electromagnetic wave, by applying Maxwell equation on Green function motion of particle is represented in form of acceleration that can be determined.